Late Onset Streptococcus agalactiae Meningitis following Early Onset Septicemia: A Preventable Disease? - Kam Lun Hon; King Hang Chan; Pak Long Ko; King Woon So; Alexander K. C. Leung (Hindawi Limited, 2017)
We report a neonate who presented with early onset Streptococcus agalactiae or group B streptococcus (GBS) septicemia within 24 hours of birth. After discharge at day 14, she went on to develop late onset GBS meningitis at 36 days of age. The infant was treated with intravenous antibiotics on both occasions and eventually discharged home with no apparent sequelae. We address issues associated with GBS infection in infancy including the demographics, risk factors, and the risk of late onset GBS meningitis following an early onset GBS infection. The major source of GBS in early onset GBS disease is maternal birth canal GBS colonization. On the other hand, nosocomial cross-infection is an important source of GBS in late onset disease. Penicillin remains the current treatment of choice for GBS infection. Given the rapid onset and progression within hours of birth and lack of an effective solution for preventing late onset GBS, administration of an effective GBS vaccine in pregnancy could provide a sensible and cost-effective solution in all settings.